2009
DOI: 10.1007/s12200-009-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Al x Ga1-x N solar-blind photodetectors grown by low pressure MOCVD

Abstract: Al x Ga 1 -x N ternary alloys are very attractive materials for application to ultraviolet (UV) photodetection. In this work, high Al content Al x Ga 1 -x N films are grown on sapphire substrate by low pressure metalorganic chemical vapor deposition (MOCVD). The Al content in the Al x Ga 1 -x N epilayer is estimated to be 54% by high resolution X-ray diffraction (HRXRD) and Vegard's law. The full width at half maximum (FWHM) of the rocking curve for the Al 0.54 Ga 0.46 N (0002) is about 597 arcsec. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In general, the Al x Ga 1− x N layers for MSM device application grow on sapphire substrates via MOCVD, MBE, sputtering method, and metal–organic vapor phase epitaxy (MOVPE) . In order to push forward with the growth of high‐quality Al x Ga 1− x N layers and also to promote the adhesion between the layers and substrates, GaN or AlN layers with thickness of tens to hundreds of nanometers were often employed as buffer or nucleation layers . It has been found that with the increase of x value, the peak response as well as the cutoff wavelengths of the MSM photodetectors manifested obvious blue transfer to shorter wavelength, an indicative of variation in the Al x Ga 1− x N bandgap.…”
Section: Iii‐nitride Compoundsmentioning
confidence: 99%
“…In general, the Al x Ga 1− x N layers for MSM device application grow on sapphire substrates via MOCVD, MBE, sputtering method, and metal–organic vapor phase epitaxy (MOVPE) . In order to push forward with the growth of high‐quality Al x Ga 1− x N layers and also to promote the adhesion between the layers and substrates, GaN or AlN layers with thickness of tens to hundreds of nanometers were often employed as buffer or nucleation layers . It has been found that with the increase of x value, the peak response as well as the cutoff wavelengths of the MSM photodetectors manifested obvious blue transfer to shorter wavelength, an indicative of variation in the Al x Ga 1− x N bandgap.…”
Section: Iii‐nitride Compoundsmentioning
confidence: 99%
“…These layers contain high densities of screw dislocations (6 x 10 8 cm -2 ) and edge dislocations (2 x 10 9 cm -2 ). Similarly, Al x Ga 1-x N (x = 0.54) films grown on sapphire substrate by low-pressure MOCVD have also been reported [8], and the films exhibited the (00.2) XRD-RC full width at half maximum (FWHM) of about 597 arcsec. It has also been reported that a thick Al x Ga 1-x N (with x = 0.6) layers on low-defect-density bulk AlN substrates could be achieved [9] with a thickness far exceeding the critical thickness as given by the Matthews and Blakeslee model.…”
Section: Introductionmentioning
confidence: 89%
“…Solenoid valve 17 is connected and disconnected according to the signal of the pressure relay, and unloading valve 18 is used in the hydraulic circuit to guarantee safety [5] . [6] [7] …”
Section: Hydraulic System Designmentioning
confidence: 99%